Richards-Klute Equation on Graphs (Моделювання, керування та інформаційні технології, 2023)
This paper contains the formulation of the problem of mass transfer in a porous medium on a graph, on the edges of which the one-dimensional problem of mass transfer is modeled using the Richards-Klute equation. To combine separate Richards-Klute equations into a single system, auxiliary mass balance equations are introduced for the vertices of the graph. Problems of approximation of these equations at the vertices of the graph are also discussed.